Representasi Perempuan dalam Narasi “Pengen Kurus” Iklan Rokok 76: Analisis Wacana Kritis Model Sara Mills - Muhammad Priadana; Syairal Fahmy Dalimunthe; Malan Lubis (Jurnal Ilmiah Wahana Pendidikan, 2026)
Advertisements, as a persuasive communication medium, not only convey information but also play a significant role in shaping social structures through language and visuals. In the context of cigarette advertisements where direct product displays are prohibited, advertisers use jokes, metaphors, and creative narratives to convey messages. This study examines the representation of women in the 76 cigarette advertisement "Pengen Kurus" (Want to be Skinny) using Sara Mills' Critical Discourse Analysis framework. The focus of the research lies in the subject-object position and the position of the reader/viewer to see how gender construction is constructed in media texts. This study uses a qualitative method with observation of advertisements as primary data and secondary sources from related literature. The analysis shows that male characters are positioned as dominant subjects who control the narrative, meanwhile, female characters are positioned as objects of ridicule related to the obsession with thinness. Women's bodies are represented not as self-authoritative but as visual products subject to patriarchal beauty standards. Audiences, at the reader level, are encouraged to laugh at female characters, thereby hegemonicly accepting thinness as a symbol of beauty while normalizing gender inequality. These findings confirm that jokes in advertising are not neutral discourse, but rather ideological instruments that perpetuate patriarchy and the symbolic abuse of women. Therefore, critical discourse analysis is crucial to dismantle biased representations of gender in the media and encourage the emergence of more just and equal constructions.